A eficiência energética do consumo de combustível em uma ferrovia heavy haul - Cabral, Eric Wilson Santos (2017)
In the Brazilian scenario from 2001 to 2015, the value of diesel rose 210%, which directly reflects the costs of the companies in the transportation segment. Among the challenges in the daily life of heavy haul railways is the cost reduction, which can be achieved by improving energy efficiency. It is then necessary to act effectively to seek the reduction of the ratio of liters of fuel consumed per Gross Ton kilometers multiplied by thousand (L/KTKB). This study aimed to identify which controlled variables in the railroads have a correlation with KTKB. Statistical analysis and continuous rail simulation tools were used, within scenarios defined according to the operational reality of a heavy haul railroad. The variables analyzed were the average weight per wagon, the number of stops of trains, average kilometers between stops (KMEP) and the type of train formation (TF). The possibility of saving with the change in the operational procedure of stops of the trains for changes of drivers was evaluated. In addition to the simulations, the fuel volume in the tank began to be monitored in real time, a system of shutdown and automatic locomotive activation was implemented and the operators were made aware of the reduction of fuel consumption. As a result, it was observed that the energy efficiency of the railway improved by 13% over the period 2014 to 2016, with a reduction in diesel consumption of 1.93 L/KTKB to 1.68 L/KTKB.